STUDI INDEKS KUALITAS TANAH SERTA BIOINDIKATOR KUALITAS AIR DI DAS MIKRO SISIM KOTA BATU - Shofie Rindi Nurhutami; Zaenal Kusuma; Istika Nita (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Landuse change causes the decrease of soil quality, so the hydrological and non-hydrological functions do not run optimally. Sisim Micro Watershedâ€˜s area of Â± 933.17 ha with a very steep slope has undergone major land-use changes. Soil Quality Index (SQI) analysis and water quality bioindicators are needed to assess the impact of land-use change. This study used 12 soil sampling plots, i.e. production forest (H2, H3, H4, H5), mixed gardens (KC2, KC3, KC4, KC5), and fields (T2, T3, T4, T5). The numbers behind the code indicate slope; 2 (slope 8-15%), 3 (slope 15-25%), 4 (slope 25-40%), and 5 (slope 40-60%). The results showed that dense vegetation and low intensity of tillage gave the best SQI. The highest SQI value was on H5 (0.63) with a good category, and the lowest was on T5 (0.32) with a bad category. The water quality bioindicator showed water pollution index of 1.97 (dirty water quality and rather heavily polluted). Soil quality which is dominated by low categories with high agricultural intensity and community waste disposal causes health condition of biotic habitats classified as unhealthy with a score of 1.90.